1978
DOI: 10.1037/0097-7403.4.4.297
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of the effects of amount of reinforcement on two response classes.

Abstract: The effects of varying amounts of reinforcement on the rate and temporal patterns of interim and terminal behaviors engendered by periodic feeding schedules were assessed in three experiments. Although the experiments differed in terms of species, response-reinforcement dependencies, and response measures, the results were consistent. Increases in amount of reinforcement appeared to have a general energizing effect on behavior. For pigeons, interim levels of general activity and terminal rates of key pecking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Rather than a weak independent variable, the problem is that absolute response rates are an insensitive dependent variable, especially at high rates of reinforcement. One of the reasons for this insensitivity are ceilings on rate: Osborne (1978) showed that general activity increased to a much greater extent with increases in amount of reinforcement than did keypecking or leverpressing.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than a weak independent variable, the problem is that absolute response rates are an insensitive dependent variable, especially at high rates of reinforcement. One of the reasons for this insensitivity are ceilings on rate: Osborne (1978) showed that general activity increased to a much greater extent with increases in amount of reinforcement than did keypecking or leverpressing.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6 provides a striking picture of the impact that such within-session satiation can have on our overall models of behavior. The top left panel shows response rates from the first 5 min of each schedule, displaying the form that Catania and Reynolds (1968) Effects of session duration and satiation similar to those shown above were found by Dougan, Kuh, and Vink (1993) and Osborne (1977). Satiation and warm-up effects can be substantial, and the mechanics of behavior provides a framework within which to derive models of them.…”
Section: Economic Translationmentioning
confidence: 98%
“…FI schedules have been shown to induce many nonreinforced behaviors (see, e.g., Anderson & Shettleworth, 1977;Roper, 1978;Staddon & Simmelhag, 1971), and the overall frequency and the temporal pattern of the reinforced behavior seems to be affected by the induced behaviors (Osborne, 1978;Staddon, 1977). Information on other behaviors occuring will provide empirical support for the tracking hypothesis and may explain two effects of the signals: the irreversibility of the effect on the response rate and the facilitation of the temporal discrimination observed in some conditions.…”
Section: Discussionmentioning
confidence: 99%